Relationship between HMGB1 content and MHC-II expression in circulating monocytes and spleen of mice challenged with zymosan - 吕艺 陆江阳 赵敏 李志宏 杨毅 (Chinese journal of traumatology, 2009)
Objective： To observe the regularity of change in high mobility group protein box 1 （HMGB 1） content in serum and spleen of mice with multiple organ dysfunction syndrome （MODS）, to analyze the correlation between HMGB 1 content and major histocompatibility complex （MHC）-II-I-Ab expression on monocytes in blood and spleen, and to explore the effect of HMGB 1 on immune function of circulating monocytes and splenocytes. Methods： One hundred 8-week-old male 57BL/6 mice were randomly divided into normal group and experimental group subdivided into 8 subgroups： 3, 8, 12 hours, 1, 2, 3, 5- 7 days and 10-12 days post zymosan injection （PZI）. MODS model was replicated by injecting zymosan into the peritoneal cavity. At each time point, blood and spleen were collected to detect HMGB 1 content and the rate of I-A^b positive monocytes. Results： In normal and PZI 3-hour, 8-hour mice, serum HMGB 1 was not detected, but it significantly increased at PZI 12 hours. In spleen of normal mice, there was low level of HMGB 1 expression. In zymosan-treated mice, HMGB 1 started to rise in spleen at PZI 3 hours. Subsequently, HMGB 1 content in both serum and spleen significantly increased, and it reached the peak level in 1-2 days, decreased in 5 days, and then increased in 10-12 days. The number of I-Ab positive monocytes in circulating blood and spleen decreased at 1-2 days （t=9.589, 4.432, P〈0.01） and 10-12 days following the challenge, forming a two trough like decrease, just corresponding with two-peak increase of HMGB 1. However, at 3 hours after zymosan challenge, I-Ab expression on circulating monocytes was downregulated （t=5.977, P〈0.01）, while that in spleen upregulated （t=4.814, P〈0.01）. Conclusion： In mice with MODS, up-regulated HMGB lexpression can regulate I-Ab expression on monocytes to depress their ability of presenting antigen, which results in immune disturbance contributing development of MODS.